The garment of infinite promise : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Huitema, Helen (Massey University, 2022)
In this project a series of textile artefacts and objects are produced as roads into engagement with the practices involved in the making of clothing and other textile practice. My own design process of interweaving technology use with handcraft methods are highlighted as being idiosyncratic to textile practice and recognisable to many practitioners. These textile artefacts are populated with familiar household settings, landscapes, and textile tools with a view to immerse viewers in nostalgia for times and practices in which they may or may not have been involved. Positive effects on mental health through involvement and learning processes of textiles are investigated through reflection and evaluation of my own practice, connected literature, and contextual information to evaluate why it may be culturally, educationally, and personally beneficial to engage in textiles practice. Furthermore, I am displaying how both the academic and practical problem-solving skills involved which form the basis of secondary school technology curriculum are contemporary and relevant. The project explores the role that textile practice including the making of garments and objects, and personal collecting of fabric or fabric stashes have played in preserving memory, evoking nostalgia, and forming collective identity in Aotearoa New Zealand. Through doing so, it calls for textiles to be more greatly valued as a discipline within the educational curriculum, thus assuring a strong future for textiles practice. Using a practice approach, it identifies the significance of textiles in our dominant western culture in relation to women's identity, and how textiles practice has been side-lined by policy makers in education. The binary between academic learning and learning-through-making is challenged through an autoethnographic reflection and evaluation of my own practice and connected literature and contextual information around attitudes to the skills and technology processes involved in the making of textiles objects and garments.
Keywords: memory; perception; nostalgia; female identity; wellbeing; emotional connection; textile skills; hand-made craft; textiles education; auto-ethnography; 330315 Textile and fashion design